(3QSGdI aj Gdadcs - (3Ydj Hf bOGeI GdHZOGOj, CHh GdMSfs
(3ChdgG (B:s
(3gPg GhQGb SWQJ ajgG CYR Gddg ehdGfG hGJbGg eG YfOi ai GdbSje s
(3BNQgG (B:s
(3GPG cGfJ gPg eQJHI dg Je fUGHgG hYdjg NJe HGHgG GYRg Gddg ai GTHGd Pjhd GdcQe hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(640) s
Keywords: (3Gdadcs